Exerting force at the maximal speed drives the increase in power output in elite athletes after 4 weeks of resistance training - Lecce, E.; Romagnoli, R.; Frinolli, G.; Felici, F.; Piacentini, M. F.; Bazzucchi, I. (European Journal of Applied Physiology, 2024)
Purpose In the present study, we examined how a 4-week intervention of maximal intended velocity (MIVRT) and controlled velocity resistance training (CRT)-induced task-specific responses in expert individuals.